Upaya Peningkatan Ketrampilan Berpikir Kritis dan Hasil Belajar Mata Pelajaran PKn melalui Metode Bermain Peran - Zahra, Rizkika Amatullah; Relmasira, Stefanus C; Juneau, Janelle Lee (Jurnal Ilmiah Sekolah Dasar, 2018)
This is a classroom action research oriented to improve students’ critical thinking skills and learning outcomes that use role playing method in Civics Education. The data will be collected using observation and evaluation sheets at the end of each cycle. Data for critical thinking skill are obtained by summing all scores of 5 indicators and divide them by the maximum scores then multiplied by 100. The result in the first cycle is 49 with category critical and there is improvement in the second cycle which score 63 with category slightly critical. Students’ learning outcome also improved from 11% before the classroom action to become 66,7% in the first cycle and become 83% in the second cycle. It proves that the use of role playing method in Civic Education can improve students’ critical thinking skills and students’ learning outcomes